2010
DOI: 10.19173/irrodl.v11i1.758
|View full text |Cite
|
Sign up to set email alerts
|

Live, online short-courses: A case study of innovative teacher professional development

Abstract: Teachers are searching for new venues through which they may meet stringent professional development requirements. Under competitive funding from NASA's (National Aeronautics and Space Administration) Office of Education and the NASA Explorer Schools Project, U.S. Satellite Laboratory, Inc. created a series of live, online, interactive short-courses. In this case study, a mixed methods analysis of a variety of data sources reveals that diverse educators from a variety of classroom contexts view the short-cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(6 reference statements)
2
11
0
Order By: Relevance
“…Bringing teachers together online for professional learning has been described using a number of terms including online teacher professional development (oTPD) (Dede, Ketelhut, Whitehouse, Breit, & McCloskey, 2009;Marrero, Woodruff, Schuster, & Riccio, 2010), professional learning communities (PLCs) (DuFour, DuFour, Eaker, & Many, 2010;Stoll & Louis, 2007), professional learning networks (PLNs) (Lieberman & Grolnick, 2005;Trust, 2012), in higher education, asynchronous learning networks (ALNs) (Hiltz, 1998;Rovai, 2002), and simply as online learning communities (Mackey & Evans, 2011). Wenger, Trayner, and de Laat (2011) In contrast, a CoP requires "the development of a shared identity around a topic or set of challenges.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bringing teachers together online for professional learning has been described using a number of terms including online teacher professional development (oTPD) (Dede, Ketelhut, Whitehouse, Breit, & McCloskey, 2009;Marrero, Woodruff, Schuster, & Riccio, 2010), professional learning communities (PLCs) (DuFour, DuFour, Eaker, & Many, 2010;Stoll & Louis, 2007), professional learning networks (PLNs) (Lieberman & Grolnick, 2005;Trust, 2012), in higher education, asynchronous learning networks (ALNs) (Hiltz, 1998;Rovai, 2002), and simply as online learning communities (Mackey & Evans, 2011). Wenger, Trayner, and de Laat (2011) In contrast, a CoP requires "the development of a shared identity around a topic or set of challenges.…”
Section: Definitionsmentioning
confidence: 99%
“…Dede's (2004aDede's ( , 2004b research described six requirements for professional development to improve education: (1) a shift from rote methods for high stakes testing to 21 st century knowledge and skills, (2) a focus on transformational strategies, (3) a shift from "make and take" professional development to ongoing teacher driven professional development, (4) a shift from passive professional development to active teacher engagement through collaborative learning communities of researchers and practitioners; (5) synchronous distributed learning opportunities that maximize available media tools, and (6) distributed learning opportunities, which are powerful mechanisms for knowledge diffusion when they exemplify practice and impart the innovations reinforcing systematic change. Collaborative online professional development was found to be desired by teachers (Marrero et al, 2010) and to expand teachers' knowledge, skills, and ideas (Glazer, Hannafin, Polly, & Rich, 2009) Almost all Canadian schools are now connected to the Internet. In a pan-Canadian survey, Plante and Beattie (2004) found that schools averaged one computer per five students, and that close to 100% of schools were connected.…”
Section: Meaningful Professional Developmentmentioning
confidence: 99%
“…Bringing teachers together online for professional learning has been described using a number of terms including online teacher professional development (oTPD) (Dede, Ketelhut, Whitehouse, Breit, & McCloskey, 2009;Marrero, Woodruff, Schuster, & Riccio, 2010), professional learning communities (PLCs) (DuFour, DuFour, Eaker, & Many, 2010;Stoll & Louis, 2007), professional learning networks (PLNs) (Lieberman & Grolnick, 2005;Trust, 2012), in higher education, asynchronous learning networks (ALNs) (Hiltz, 1998;Rovai, 2002), and simply as online learning communities (Mackey & Evans, 2011). In contrast, a CoP requires "the development of a shared identity around a topic or set of challenges.…”
Section: Definitionsmentioning
confidence: 99%
“…Professional development should focus on self-directed learning in the authentic settings that occur while planning, reflecting, and sharing personal learning experiences (Mushayikwa & Lubben, 2009); learning together with one's peers (Boyle, White, & Boyle, 2004); and participating at collaborative knowledgebuilding events (Scardamalia & Bereiter, 2003). A study by Marrero, Woodruff, Schuster, and Riccio (2010) indicated that teachers who participated in online courses and learnt together with peers found this form of learning more supportive than traditional professional development workshops. Online professional development may provide opportunities for integrating teachers' experiences as learners and teachers, claim Mackey and Evans (2011).…”
Section: Introductionmentioning
confidence: 99%